2016
DOI: 10.1186/s13075-016-1101-3
|View full text |Cite
|
Sign up to set email alerts
|

Rituximab induces phenotypical and functional changes of NK cells in a non-malignant experimental setting

Abstract: BackgroundRituximab has broad and increasing application in rheumatic diseases. It is known from lymphoma studies that natural killer (NK) cells can lyse rituximab-coated transformed B cells. However, the role of NK cells in mediating rituximab-induced depletion of non-malignant B cells is unknown. The purpose of this study was to provide fundamental data on rituximab-mediated effects on NK cells in PBMCs without tumor cells, in order to simulate effects that could be relevant in patients with rheumatic diseas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(30 citation statements)
references
References 33 publications
0
29
1
Order By: Relevance
“…Furthermore, the glyco-engineered Obinutuzumab appears to be less affected by the inhibitory effects of KIR/HLA ligation compared to Rituximab (220). Several lines of evidence, from in-vitro and animal studies show that NK cells are involved in the mechanism of action of Rituximab/ Obinutuzumab (221)(222)(223)(224), yet their exact role in clinical settings are not completely understood. A recent clinical study suggested that lower peripheral NK cell counts in follicular lymphoma and lower peripheral and tumor infiltrated NK cell numbers in diffuse large B-cell lymphoma associate with transient progression-free survival in response to therapy (225).…”
Section: Nct02240706 Nct02632721mentioning
confidence: 99%
“…Furthermore, the glyco-engineered Obinutuzumab appears to be less affected by the inhibitory effects of KIR/HLA ligation compared to Rituximab (220). Several lines of evidence, from in-vitro and animal studies show that NK cells are involved in the mechanism of action of Rituximab/ Obinutuzumab (221)(222)(223)(224), yet their exact role in clinical settings are not completely understood. A recent clinical study suggested that lower peripheral NK cell counts in follicular lymphoma and lower peripheral and tumor infiltrated NK cell numbers in diffuse large B-cell lymphoma associate with transient progression-free survival in response to therapy (225).…”
Section: Nct02240706 Nct02632721mentioning
confidence: 99%
“…To assess possible changes in NK cell function after TransIT-TKO transfection, we performed cytotoxicity assays using K562 to measure direct killing [32], and Rituximab (RTX)-coated autologous B cells to measure ADCC [33]. Prior to each assay, target cells (K562 or RTXcoated B cells) were stained with cell trace violet (CTV) (Thermofisher).…”
Section: Degranulation and Cytotoxicity Assaysmentioning
confidence: 99%
“…By virtue of the high expression of CD16 (Fc-ɣ-Receptor IIIa), NK cells can also be targeted via the Fc-part of therapeutic antibodies, which induces ADCC [6,12]. NK cells thus play a role in the treatment with cell-depleting antibodies [13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%